COMPARISON OF COSEISMIC IONOSPHERIC DISTURBANCE WAVEFORMS REVISITED: STRIKE-SLIP, NORMAL, AND REVERSE FAULT EARTHQUAKE - Cahyadi , Mokhamad Nur (Departemen Teknik Geomatika ITS, 2014)
Using Total Electron Content (TEC) measurements with Global Positioning System we studied ionospheric responses to three large earthquakes with difference focal mechanism that occurred in the Sumatra Andaman 26 December 2004, North off Sumatra 11 April 2012, and North Japan 7 December 2012. These earthquakes have different focal mechanisms, i.e. high-angle reverse, strike-slip, and normal faulting, respectively. TEC responses to the Sumatra Andaman 2004 and north Japan 2012 events initiated with positive changes. On the other hand, the initial TEC changes in the Sumatra 2012 earthquake showed both positive and negative polarities depending on the azimuth around the focal area. Such a variety may reflect differences in coseismic vertical crustal displacements, which are dominated by uplift and subsidence in the Sumatra 2012 event. This phenomena has same characteristic with 1994 Kuril Arch earthquake. There are three different propagation velocity in the Sumatra 2012 earthquake, within the first 300 km until 430 km, the CID propagation velocity was 3 km/s, which is equal to the secod sound speed at the height of the ionospheric F-layer. Starting from 380 km until 750 km out from the epicenter, the disturbance seems to divide into two separate perturbations, with each propagating at a different velocity, about 1 km/s for the one and about 0.4 m/s for the other. The apparent velocity in the Sumatra Andaman 2004 and Japan 2012 propagated 1 km/s and 0.3 km/s, consistent with the sound speed at the ionospheric F layer height and internal gravity wave respectively. Resonant oscillation of TEC with a frequency of 3.7 mHZ and 4.4 mHz have been found in the Sumatra 2012 and Sumatra Andaman 2004 events. Those earthquakes, which occurred during a period of quiet geomagnetic activity, also showed clear preseismic TEC anomalies similar to those before the 2011 Tohoku-Oki and 2007 Bengkulu earthquake. The positive anomalies started 30-60 minutes before the earthquake to the north of the fault region. However, preseismic ionospheric anomalies of the 2012 Japan earthquake could not be observed because moment magnitude of the earthquake is smaller than Mw 8.2